Ultrasound-Assisted Extraction of Fennel Leaves: Process optimization, Thin Layer Chromatography and Cytotoxic Activity of Ethanolic Extract - Abdul-lalil, Thukaa zuhair (Iraqi Journal of Pharmaceutical Sciences, 2024)
Foeniculum vulgare commonly known as fennel belonging to the family Umbelliferae, is cultivated throughout the world as a spices as well as medicinal plant possessing antimicrobial, antidiabetic, antioxidant, anti-inflammatory, …etc. A Single Factor Experiment analysis has been employed in this study to optimize caffiec acid extraction from fennel leaves by ultrasound assisted extraction method in which three variables single factor examined which were ethanol concentration, extraction time and ultrasound frequency. The study’s objective was to assess the effects of variables chosen on caffiec acid’s extraction performance, preliminary evaluated by thin layer chromatography (TLC) and evaluate the cytotoxic effect of optimized ethanolic extract of this plant on human breast cancer (MDA-MB-468) cell line. the experimental results revealed that the most influential extraction variables were: 80% ethanol as extraction solvent, 15 min was the time to achieve the good extraction efficacy and 40 KHz ultrasound frequency and The IC50 value of the cytotoxic effect (P < 0.05) of optimized ethanolic extract of Iraqi Foeniculum vulgare leaves on MDA-MB-468 cell line after 72 h of incubation were significantly high (46.89 µg/ml). The results of this study will be used to create a natural medicine for the symptoms of various diseases and to standardize the processes for extracting caffeic acid from natural items, particularly fennel.